Hypertrophic olivary degeneration: a 7 Tesla advanced imaging case report - Calzoni, Tommaso; Donatelli, Graziella; Migaleddu, Gianmichele; Lancione, Marta; Cecchi, Paolo; Biagi, Laura; Caniglia, Michele; Ceravolo, Roberto; Cosottini, Mirco (Frontiers in Neuroscience, 2025)
Background and objectivesA 50-year-old patient developed ataxia, nystagmus, and palatal tremor. Conventional magnetic resonance imaging (MRI) revealed inferior olivary nuclei enlargement and hyperintensity in T2-weighted images, indicating hypertrophic olivary degeneration (HOD). The patient’s past medical history reported proton therapy for an VIII cranial nerve Schwannoma. Here, we aimed to investigate the potential alterations involving tracts and nuclei composing the dentato-rubro-olivary pathway (Guillain-Mollaret triangle) using an advanced ultra-high field (7 T) MRI protocol.Materials and methodsThe patient underwent a 7 T-MRI brain exam, including a multi-echo gradient-echo sequence for quantitative susceptibility mapping and diffusion tensor imaging (DTI). The DTI dataset was elaborated for tractography and computation of tensor metrics.Results7 T-MRI allowed the depiction of the brainstem tracts and nuclei composing the Guillain-Mollaret triangle. Both qualitative and quantitative analyses of these structures demonstrated damage to the right red nucleus and the dentato-rubral tracts bilaterally. These findings are consistent with the pathophysiology of HOD and were confirmed in a follow-up MRI.DiscussionThis study highlights the capability of 7 T-MRI to depict and investigate brainstem substructures such as tracts and nuclei. To the best of our knowledge, this is the first study to depict all tracts composing the Guillain-Mollaret triangle and directly document their alterations in HOD.